Evaluasi Ms Glow: Brand Ambassador Bukan Korea, Buy Or No? - Anisah Aulia; Gina Apryani Nurunnisha (Syntax Literate, 2023)
The development of the internet and technology affects the lifestyle and buying interest of consumers which can trigger various companies to carry out superior marketing strategies and ways in order to attract consumer buying interest. To maintain brand image and attract consumers, the company utilizes brand ambassadors who are in the spotlight and have a beautiful and beautiful image. This is different from what is done by the Ms Glow brand which attracts BA which does not have high popularity in Indonesia which is far from a beautiful and beautiful image. Babe Cabita and Marshel Widianto were recruited to become BA Ms Glow. Both brand ambassadors are comedians who are famous not for their beautiful image but because of their joke material. Although the two BA Ms Glow are far from beautiful images, Ms Glow's search volume actually increased in the period from July to September 2021. In addition, Ms. Glow's popularity also continues to increase when compared to competitors. This is evident from the comparison of the trend chart between Ms Glow and avoskin from February 25 to April 2021 with the results of the Ms Glow chart which increased rapidly compared to avoskin. Because the phenomenon that occurs is different from the phenomenon in general, the researcher tried to conduct the study and find out how the influence of brand ambassadors and brand image on consumer buying interest. Researchers use quantitative descriptive methods by collecting and interpreting data and results. Based on the research conducted, it was found that brand ambassadors and brand image have a significant effect on consumer buying interest.